The Influence of Product Quality, Brand Image on Purchasing Decisions through Brand Trust as Mediating Variable - Hapsoro, Bayu Bagas; Hafidh, Wildan Ainul (Management Analysis Journal, 2018)
The aim of the study is to examine the effect of product quality and brand image on purchasing decisions throught brand trust. The population in this study is the consumers of Sambal Terasi Siap Pakai (Ready to use shrimp paste sauce) product from ABC brand in Semarang and applying incindental sampling. Questionaire used instrument test, descriptive analysis, classic assumption test, partial test and path analysis. The data was analysed by SPSS 21 software for Windows. This study found that product quality has a positive effect on brand trust, brand image has a positive effect on brand trust, brand image has a positive effect on brand trust, product quality has positive effect on purchasing decision, brand trust has a positive effect on purchasing decision, product quality has a positive positife effectbon purchasing decision throught brand trust, brand image has a positive effect on purchasing decision throught brand trust.